Respuesta :
A = lw + wh + lh Subtract lh from both sides
A - lh = lw + wh Factor out the w
A - lh = w (l + h) Divide both sides by (l + h)
[tex] \frac{A - lh}{l + h}[/tex] = w Switch the sides to make it easier to read
w = [tex] \frac{A - lh}{l + h}[/tex]
A - lh = lw + wh Factor out the w
A - lh = w (l + h) Divide both sides by (l + h)
[tex] \frac{A - lh}{l + h}[/tex] = w Switch the sides to make it easier to read
w = [tex] \frac{A - lh}{l + h}[/tex]
Making w the subject of formula is [tex]w = \frac{A - lh}{l + h}[/tex]
In this exercise, you're required to solve for w in the mathematical (algebraic) expression by making it the subject of formula.
Given the following mathematical (algebraic) expression;
[tex]A = lw + wh + lh[/tex]
We would simplify by moving the variables with w;
[tex]lw + wh = A - lh[/tex]
Factorizing w, we have;
[tex]w(l + h) = A - lh[/tex]
Simplifying further, we have;
[tex]w = \frac{A - lh}{l + h}[/tex]
Therefore, making w the subject of formula is [tex]w = \frac{A - lh}{l + h}[/tex]
Find more information: https://brainly.com/question/21866313